Linear Body Measurements Of Grower Rabbits Fed Shea Butter Nut Meal In North Central Nigeria (2016)
There is a high demand for rabbit either as meat, pet or laboratory animal. However, its production is still at subsistence level in Nigeria. This could be due to the rising competition between man and livestock for conventional feeds tuffs. This study was aimed at investigating the suitability of shea butter nut meal (SBNM as an unconventional fee d stuff in rabbit diets. A total of 36 rabbits weighing about 1.2kg at 7wks old, were fed 0.0% (TJ, 2.0% (TJ and 6.0% (TJ SBNM for eight weeks. The results indicated significant differences (P<0.05) among the treatments. Body weight gain values ranged from 0.03g to 0.26g. The hind limb length varied 'from 0 .1 3 - 0.38cm, hair length (0.07 - 0.16cm) and the chest circumference value varied from 0.1 - 0.33cm. Although, it was observed that the values of growth indices monitored did not follow a definite trend among the treatments. There was an increase in value of all the parameters measured throughout the study period. Thus, SBNM may probably be a suitable feedstuff at 6.0% inclusion in rabbit grower diets.